Anomalous diffusion in Gibbsian-breaking of wealth distributions - W.A.T, Wan Abdullah; S.M., Khidzir (Malaysian Journal of Science, 2010)
In a conservative system, energy equipartition results in a Boltzmann-Gibbs distribution. This is also expected in an ergodic kinetic economy if wealth is conserved. Empirical data however has shown the existence of a regime with a power law distribution. In models albeit with conservative wealth, we show that this arises due to anomalous diffusion.